Improving Students’ Reading Comprehension Using Power Point Presentation - Indah Muzdalifah (Universitas Lancang Kuning, 2016)
The purpose of this research was to find out and explain the using of power point presentation in improvingstudents’ reading comprehension of short functional texts and to find out and explain the factors that influences the changes of students’ reading comprehension of short functional texts. Design of this research was classroom action research. The researcher used test as instrument that was reading texts. The result of analyzing data showed that the students’ scores could increase the students’ reading comprehension of short functional text. This improvement is influenced by several factors. The first factor is material. The choice of material which can invite the students’ interaction is very important. The material of reading short functional text should be new, various and relevant with the students’ reality life. Thus, it can make them interested in watching the material.